Autopercepção estética e qualidade de vida de pacientes submetidos a dois protocolos de tratamento para a fluorose dentária: estudo longitudinal - Sousa, Bruno Vieira de (2017)
The objective was to evaluate, after six years, the self-perception of the dental aesthetics and quality of life of the participants submitted to two treatment protocols for the removal of spots on the teeth enamel affected by dental fluorosis. The sample consisted of 33 participants who underwent the treatments in the initial intervention and could be interviewed again. These were divided into two groups according to the treatment protocol received. G1 - microabrasion (n = 17) and G2 - microabrasion associated with home tooth whitening (n = 16). The evaluation of improvement in dental appearance was performed through a visual analogue scale, ranging from 1 (None) to 7 (Excellent). The participants answered a questionnaire of aesthetic perception and impact of dental fluorosis, which observes the concerns in the physical, mental and social domains, including the color of the teeth. The impact of the treatments on the individuals' capacity to perform their daily activities was verified through Oral Impact on Daily Performances (OIDP). The results show a good satisfaction of the participants of both groups regarding the improvement in dental aesthetics. The perception questionnaire revealed a small discomfort with the appearance of the teeth, especially in relation to the staining, however, these conditions do not worry the majority or prevent them from smiling spontaneously. Eating and cleaning the mouth were the main activities affected by the oral health condition of the interviewees. Even after six years, the proposed treatments were effective, however, there was no statistical difference between the aspects perceived in the majority of individuals who received only microabrasion or microabrasion associated with dental bleaching.